Monetary Union Stability: The Need for a Government Banker and the Case for a European Public Finance Authority - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2011)
This paper argues monetary union stability requires a government banker that manages the bond market and it offers a specific proposal for stabilizing the euro that does not violate the no country bail-out clause. There is accumulating evidence that the euro's current architecture is unstable. The source of instability is high interest rates on highly indebted countries which creates unsustainable debt burdens. Remedying this problem requires a central bank that acts as government banker and pushes down government bond interest rates to sustainable levels. That can be accomplished by creation of a European Public Finance Authority (EPFA) that issues public debt which the European Central Bank (ECB) is allowed to trade. The debate over the euro's financial architecture also has significant political implications. That is because the current neoliberal inspired architecture, which imposes a complete separation between the central bank and public finances, puts governments under continuous financial pressures. Over time, that pressure makes it difficult to maintain the European social democratic welfare state. This gives a political reason for reforming the euro and creating an EPFA that supplements the economic case for reform.
urn:nbn:de:101:1-201202285175
Keywords: 330; monetary union; stability; government banker; euro.; Eurozone; Wirtschaftliche Instabilität; Geldpolitik; Finanzpolitik; Internationale Wirtschaftspolitik; Öffentliche Anleihe; Wertpapierhandel; Eurozone